Angiogenesis Inhibitor Z24 Induces Endothelial Cell Apoptosis and Suppresses Tumor Growth and Metastasis - Haiyan Lu; Chen Lin; Zhibing Zheng; Song Li; Shunxing Guo; Xueyan Zhang; Ming Fu; Xiao Liang; Min Wu (Elsevier, 2005)
Z24, a small molecular compound with similar chemical structure to SU5416 designed and synthesized by our lab, has been proved to be an angiogenesis inhibitor. In this study, Z24 was shown to induce human umbilical venous endothelial cell (HUVEC) apoptosis confirmed by morphologic changes including the presence of apoptotic bodies, significant apoptotic sub-G1 peak upon flow-cytometric analysis, formation of DNA ladders upon agarose gel electrophoresis, and TUNEL (TdT mediated X-dUTP nick-end labeling) results. Systemic administration of Z24 at non-toxic dose in nude mice resulted in inhibition of subcutaneous tumor growth of human colon cancer HCT-8, while it did not inhibit this cell line in vitro, with 100-fold more potent growth-inhibition against endothelial cells. The immunohistochemical results showed that the microvessel density of tumor tissue of the Z24 group was significantly lower than that of the control groups (P<0.05), which supported its anti-angiogenic property. We further found that Z24 inhibited the pulmonary metastasis of mouse lung adenocarcinoma LA795, with fewer surface lung metastases (89.6%, P<0.0001) and decreased lung weights (38.5%, P<0.01) compared to the vehicle group. All these findings support that Z24 is a promising angiogenesis inhibitor for limiting tumor growth and metastasis. Keywords:: Z24, angiogenesis inhibitor, tumor growth and metastasis, microvessel density, endothelial cell apoptosis